Elite Monopoly: Provisions Before The General Election - Nabila Nikmatul Laeli; Arini Dina Kamala; Zhila Jannati (Jurnal Komunikasi Islam dan Kehumasan (JKPI), 2023)
When the general election day is upcoming, the media outset to actively fulfill the news headline with political issues, especially presidential candidates. One of them is the monopoly game a new concept of political talk that has been presented by media for a long time. This phenomenon is interesting and recorded high responses from public as spectator in the comments column since it was uploaded. Hence, the researcher determine to analyze the audiences’ responses to media creativity in creating renewal of discussion patterns by using descriptive qualitative approach and Struat Hall's reception theory. The descriptive analysis was formulated based on literature review of media sources and related literature. The results of the analysis show that the creative presentation of political education through the media attracts public interest in supporting the upcoming election day which is the goals of Indonesian democracy.